Camera trapping as a novel method for monitoring North Island brown kiwi (Apteryx mantelli) and implications in environmental management : a thesis presented in partial fulfilment of the requirements for the degree of Master of Environmental Management, Massey University, New Zealand - Fan, Nathan (Massey University, 2023)
This thesis focused on the use of camera-trapping as a monitoring method for the North Island brown kiwi (Apteryx mantelli). Brown kiwi is a species of conservation concern and there is a need for methods that allow the monitoring of population numbers and trajectories to inform conservation practices. Traditional monitoring tools for brown kiwi are either invasive or labour intensive, and camera-trapping offers a cost-effective and less invasive alternative. This thesis utilizes camera trap data collected between 2014 and 2017 for a feral cat study (Strang, 2018) on South Ponui, a beef and sheep farm in the Auckland area. The objectives of this study were to assess the possibility of camera-trapping for monitoring brown kiwi by investigating camera trap placement strategies to optimize capture rates, exploring the camera trap rates in fragmented habitats compared to the continuous forest, and determining the effect of the number of cameras on capture rate. Little is known about how brown kiwi use agricultural land. However, this knowledge is important because agricultural lands cover approximately 40% of New Zealand and an expected spinoff of Predator Free New Zealand 2050, a project aiming at eradicating introduced predators by the year 2050, is that native species could expand their range into agricultural lands. Therefore, I examined the nocturnal habitat utilization of brown kiwi and provided management strategies for their future conservation on agricultural lands. Strang deployed from six to 28 camera traps to 28 fixed locations in a 36 ha sampling grid (Strang, 2018). I analyzed the video data using generalized linear mixed models (GLMMs) and heat maps. The findings indicated that camera-trapping was effective in monitoring brown kiwi, including in assessing their nocturnal habitat utilization. The study revealed that brown kiwi predominantly utilize forest habitats during their nocturnal activities, followed by scrub and pasture edge habitats. Three camera trap placement strategies were identified to maximize capture rates, including positioning traps in forests or edge habitats on gentle or steep slopes, with autumn and winter identified as optimal seasons for monitoring. The study also revealed that camera traps placed in fragmented habitats maintained their GLMMs predictive ability compared to the cameras placed in continuous habitats. Additionally, by reducing the number of cameras, it is determined that if the grid cell size does not exceed 37 ha per camera, the GLMM prediction ability remains consistent. These findings have management implications, emphasizing the importance of intensive predator control in forests and edge habitats bordering pastures, preserving, and increasing native forest patches on farms, and controlling livestock access to forests. The attraction of brown kiwi to fragmented habitats underscores the need to safeguard remnants of native forests on agricultural lands, facilitating their dispersal across the landscape. Moreover, the study suggests that incorporating camera-trapping into the brown kiwi monitoring toolbox offers benefits such as scaling up management efforts, increasing community engagement, and reducing long-term costs. Ultimately, these findings contribute to the understanding and conservation of the North Island brown kiwi.
Keywords: 410407 Wildlife and habitat management